Hygrothermal performance of a new thermal aerogel-based render under distinct climatic conditions - Joana F. Maia (2021)
Silica-aerogel is one of the nanomaterials that contributes to increasing the thermal properties, due to its high porosity and low density, and also low thermal conductivity. The development of innovative thermal renderings is a current trend, but their impact on the hygrothermal performance of facade systems requires additional investigation. The main goal of the present work consists of discussing the hygrothermal performance of a new thermal aerogel-based render when applied as a component of a multilayer coating system. To achieve this objective, relevant hygrothermal properties were determined. An accurate analysis of the hygrothermal impact, considering different European climates, was also performed. A clear improvement of the thermal conductivity of the new render, at dry-state, (0.029 W/m.degrees C) was found. As the observed high open porosity (approximate to 83%) leads to a high capillary absorption coefficient (0.129 kg/m(2).s(1/2)), the prevention of moisture-related risks is a critical issue. Due to the high increase of the thermal conductivity (up to 400%), when saturated, the application of finishing materials is therefore decisive for the successful use of these renders in building envelopes. The numerical simulations highlighted significant hygrothermal risks at higher latitudes, observed by relevant temperature differences across the render thickness and significant external condensation potential.